Rancang Bangun Aplikasi Media Promosi Pariwisata dan Kebudayaan Kabupaten Kuningan Berbasis Web - Tito Sugiharto (ISB Atma Luhur, 2015)
This research was made with the goal of producing an app to promote tourism and culture in Kuningan Regency based web. The problem in this research is the need to build a web based application media campaign to increase the number of tourists visiting the Kuningan Regency. The research objective to be achieved is the application of media promotion of tourism and culture that attract web based and can accessed using the Internet. With the application of promotional media is expected to increase the number of tourists visiting the Kuningan Regency. This study will discuss how to design and develop application Kuningan Regency tourism and culture based web. With this application, the tourists can get information about the existence of diversity of tourism in the Kuningan Regency. In the process of making this application used the methodology of system design and cultural tourism application is built using the PHP programming language and MySQL database. These applications can be run via a browser connected to the Internet.